The Heart of the Matter: How Reforms Unsettle Organizational Identity. Issue 6 (September 2019) - Neumerski, Christine M.; Cohen, David K.
The identity of public school systems changed dramatically over the past 25 years, as standards-based reform held schools accountable for more equal and academically demanding education for poorer and more diverse students. We argue that identity also changed in private and hybrid school systems. Drawing on semistructured interviews with 40 school system leaders, we examine the ways in which three different school systems – a Montessori, Center, an urban Catholic system, and the International Baccalaureate – responded to the new conditions that reforms, poverty, and migration brought to the United States. We find that leaders perceived the identity of their systems as changing, as they questioned how much the systems should adapt to the new education sector.